MAEA is an E3 ubiquitin ligase promoting autophagy and maintenance of haematopoietic stem cells - Qiaozhi Wei (Nature Portfolio, 2021)
Haematopoietic stem cells (HSCs) are metabolically quiescent, with balanced myeloid and lymphoid potential. Here the authors show that MAEA is required in HSCs for ubiquitination and downregulation of surface cytokine receptors via autophagy; MAEA loss leads to impaired HSC quiescence and a myeloproliferative disorder.